Preparation of microspheres of carbon black dispersion in uranyl-ascorbate gels as precursors for uranium carbide. (May 2016) - Brykala, Marcin; Rogowski, Marcin
Abstract: A novel technique to fabricate precursors of carbide-ceramic nuclear fuel via synthesis of spherical particles (with a diameter below 150 μm) of carbon black dispersion in uranyl-ascorbate gels by a combination of the Complex Sol–Gel Process and the Double Extraction Process has been elaborated. Applying of ascorbic acid as complexing agent in the Complex Sol–Gel Process allows to obtain stable and uniform dispersion of carbon in an uranyl-ascorbate sol. Traditionally, the dispersability is improved by employment of dispersing agents – surfactants. In the presented Complex Sol–Gel Process, a dispersing agent is needless. The ascorbate sols perfectly wet carbon black and do not form agglomerates. In the Double Extraction Process, dispersion of carbon black in sols is emulsified by drops in the organic phase consisting of 2-ethylhexanol-1 and 1 volume % of Primene JM-T. The microspheres are created by gelation of droplets, through simultaneous extraction of water with 2-ethylhexanol-1 and nitrate ions with Primene JM-T. The elaboration of the optimal gelation conditions requires considering many issues which are described in this paper. Highlights: Elaboration of method of gelation dispersion of carbon black in uranyl-ascorbate gel. Gelation of dispersion to microspheres (Ø<150 μm). Applying of ascorbic acid in the method allows to obtain stable and uniform dispersion. Applying of ascorbic acid eliminates of application of dispersing agents. Fabrication of precursors for uranium carbide microspheres.